Survival. Volume 67, number 3, global politics and strategy (Routledge, 2025)
Survival, the IISS's bimonthly journal, challenges conventional wisdom and brings fresh, often controversial, perspectives on strategic issues of the moment.In this issue: Lawrence Freedman assesses the sufficiency of the British and French nuclear deterrents for Europe in light of Russian revanchism and the United States' strategic distancing from Europe Bence Nemeth argues that, as speed becomes more critical than funding for European defence, front-line states in particular should undertake national military preparations before focusing on multinational integration Mariya Grinberg examines how the development of nuclear weapons has discouraged future use of economic warfare Steven Simon appraises Trump's first hundred days and the tenuousness of the American project And eight other thought-provoking pieces, as well as our regular Book Reviews and Noteworthy column To read free articles from the journal, please visit its homepage at https://www.tandfonline.com/journals/tsur20.Editor: Dr Dana AllinManaging Editor: Jonathan StevensonAssociate Editor: Carolyn WestEditorial Assistant: Anna Gallagher